Treponema denticola-Induced RASA4 Upregulation Mediates Cytoskeletal Dysfunction and MMP-2 Activity in Periodontal Fibroblasts - Malone, Erin Trent; Ganther, Sean; Mena, Nevina; Radaic, Allan; Shariati, Keemia; Kindberg, Abigail; Tafolla, Christian; Kamarajan, Pachiyappan; Fenno, J. Christopher; Zhan, Ling; Kapila, Yvonne L. (Frontiers in Cellular and Infection Microbiology, 2021)
The periodontal complex consists of the periodontal ligament (PDL), alveolar bone, and cementum, which work together to turn mechanical load into biological responses that are responsible for maintaining a homeostatic environment. However oral microbes, under conditions of dysbiosis, may challenge the actin dynamic properties of the PDL in the context of periodontal disease. To study this process, we examined host-microbial interactions in the context of the periodontium via molecular and functional cell assays and showed that human PDL cell interactions with Treponema denticola induce actin depolymerization through a novel actin reorganization signaling mechanism. This actin reorganization mechanism and loss of cell adhesion is a pathological response characterized by an initial upregulation of RASA4 mRNA expression resulting in an increase in matrix metalloproteinase-2 activity. This mechanism is specific to the T. denticola effector protein, dentilisin, thereby uncovering a novel effect for Treponema denticola-mediated RASA4 transcriptional activation and actin depolymerization in primary human PDL cells.